2016
DOI: 10.1016/j.addbeh.2015.08.001
|View full text |Cite
|
Sign up to set email alerts
|

The role of social drinking factors in the relationship between incapacitated sexual assault and drinking before sexual activity

Abstract: The White House Council (2014) has highlighted sexual assault prevention as a high priority issue in need of immediate attention. A risk factor associated with sexual assault victimization and revictimization is drinking before sexual activity. The current study examined the relationship between incapacitated sexual assault (ISA) and drinking before sexual activity. Additionally, social-related drinking factors including drinking to conform motives, social drinking motives, and perceived drinking norms were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 65 publications
1
12
0
3
Order By: Relevance
“…One item assessed for the frequency with which individuals had consumed alcohol prior to or during sexual activity (as used previously in Bird, Gilmore, George, & Lewis, 2016). Response options ranged on a 5-point scale (0 = never , 1 = about a quarter of the time , 2 = about half the time , 3 = about three quarters of the time , and 4 = always ).…”
Section: Methodsmentioning
confidence: 99%
“…One item assessed for the frequency with which individuals had consumed alcohol prior to or during sexual activity (as used previously in Bird, Gilmore, George, & Lewis, 2016). Response options ranged on a 5-point scale (0 = never , 1 = about a quarter of the time , 2 = about half the time , 3 = about three quarters of the time , and 4 = always ).…”
Section: Methodsmentioning
confidence: 99%
“…It was found that the consumption of Sopi drinks was related to social relationships among teens, as well as the existence of social motives, following peers or just peer pressure to celebrate happiness together [10]. The relationship between them affects behavior, especially the behavior of alcohol consumption [11,12]. Teens who drink Sopi will feel an increase in mood, increase in energy levels, be more energized and more confident in speaking and ready to act.…”
Section: Sopi For Social Kinshipmentioning
confidence: 99%
“…Até certo ponto, onde o consumo de álcool tenha esse papel de alívio de tensões, é compreensível que a avaliação dos adolescentes sobre o relacionamento entre os seus pais não se expresse de forma negativa. É comum o uso de bebidas alcoólicas para superar situações de maior exigência em termos de habilidades sociais, como entrar em contato com desconhecidos no espaço público, em situações de preparação para a atividade sexual 10,25 ou pensando em se divertir mais ou para atenuar emoções negativas 25 , condições favorecedoras do consumo que têm sido descritas tanto para populações adultas como para adolescentes.…”
Section: áLcool E Relação Dos Paisunclassified
“…Tais manifestações podem fazer com que a convivência pareça melhor ou mais harmônica, desafios pareçam mais facilmente transponíveis, as pessoas se coloquem de modo mais confortável e os conflitos fiquem menos expostos 4 . Isso é especialmente evidente quando se analisam prevalências de consumo de bebidas alcoólicas entre jovens diante de desafios sociais, como em momentos que antecedem relações sexuais 10 . De maneira geral, o consumo de álcool começa ainda na adolescência 1,2 , e o padrão de consumo está intimamente relacionado com o tipo de relacionamento existente entre o adolescente e seus pais [11][12][13][14][15] .…”
Section: Introductionunclassified